Penyakit Busuk Akar dan Pangkal Batang Tebu di Sumatera Selatan - Maryono, Tri; Widiastuti, Ani; Priyatmojo, Achmadi (Jurnal Fitopatologi Indonesia, 2017)
Root and basal stem rot disease caused by Xylaria sp. is a new diseases in Indonesian sugarcane plantation. The disease has been reported only occurred in sugarcane plantations in Sumatera. Limited information about the disease has slowed down disease diagnosis in the field. The research was aimed to describe symptoms, signs, and spatial distribution of the disease caused by Xylaria. A survey was conducted at a sugarcane plantation in South Sumatera (3° 26’ 16.6” S dan 104°40’ 09.8” E). Typical symptoms of the disease involved drying of all leaves and plant death, dry rot of root and basal stem, and retarded growth of ratoon cane were recorded. Stroma was found on surface of diseased stems and on soil surface of diseased plants, and spatial aggregation of diseased plants was observed in all locations. The distribution of the diseased plant aggregately and the presence of stroma on diseased plants are important characteristics of the disease diagnosis in sugarcane plantations.